Optimizing Incident Management With Itil V4 Framework For Internet Network Stability At Mahardika Institute Of Technology And Health Cirebon - Ahmad Ngiliyun; Franciskus Antonius Alijoyo (Journal of Innovative and Creativity, 2025)
In the evolving digital era, computer networks have become vital infrastructure for various institutions and organizations, including educational institutions such as the Mahardika Institute of Technology and Health. At the same time, network instability can cause disruptions in daily activities, including teaching and learning activities, access to information resources, and various other support services. This research aims to identify and address network instability at the Mahardika Institute of Technology and Health using a Case Study research method.